High‐Pressure Accelerated Enantioselective Addition of Indoles to Trifluoromethyl Ketones with a Low Loading of Chiral BINOL‐Derived Phosphoric Acid. Issue 13 (5th June 2017) - Biedrzycki, Michał; Kasztelan, Adrian; Kwiatkowski, Piotr
Abstract: The effect of pressure (up to 10 kbar) on the Brønsted acid catalyzed enantioselective hydroxyalkylation of indoles with trifluoromethyl ketones was explored. The reaction was effectively accelerated at 9 kbar with a very low loading of a 1, 1′‐bi‐2‐naphthol (BINOL) ‐derived phosphoric acid (0.05–0.2 mol % of TRIP) and provided the products with high enantioselectivity (84–98 % ee ). Abstract : Faster under pressure : The first application of chiral phosphoric acids as catalysts under hyperbaric conditions is reported. The reaction of indoles with trifluoromethyl ketones is effectively accelerated at 9 kbar (1 kbar=100 MPa) with a very low loading of a 1, 1′‐bi‐2‐naphthol (BINOL)‐derived phosphoric acid (0.05–0.2 mol % of TRIP) and gives the products with high enantioselectivity (up to 98 % ee ).